Studi Prevalensi Infeksi Cacing Ascaris lumbricoides pada Siswa SDN Tanjung Duren Selatan 01 Pagi, Jakarta Barat - Wandi Wandi; Esther Sri Majawati (Fakultas Kedokteran Universitas Kristen Krida Wacana, 2018)
In Indonesia, intestinal worms diseases have become a public health problem in both rural and urban areas. Even though these diseases have a great impact on the quality of human resources, but this problem does not get much attention from the public. This study aimed to determine the prevalence of Ascaris lumbricoides infection in SDN Tanjung Duren 01 Pagi, West Jakarta. This research is a descriptive study with a cross sectional approach. Among 90 respondents, one student was infected by Ascaris lumbricoides. The infection can be caused by personal hygiene factors such as hand washing, nail biting, nail clipping, school snacking, and eating habits of using cutleries, as well as habit of playing on the ground,. Low Ascaris lumbricoides infection is thought to be associated with environmental sanitation in schools and personal hygiene.Keywords: Ascaris lumbricoides, personal hygiene, environmental sanitation